Hubungan Usia dan Pengetahuan Dengan Kekurangan Energi Kronik Pada Ibu Hamil di Puskesmas Glagah Kecamatan Pakuniran - Jely Anggraeni; Iit Ermawati; Tutik Ekasari (STIKes Ibnu Sina Ajibarang, 2025)
Lack of nutrients during pregnancy can cause fetal growth disorders because during pregnancy there is an increase in energy and nutrient metabolism, this increase is aimed at fetal growth and development. There are many factors that cause chronic energy deficiency, including age and knowledge. The aim of this research is to determine the relationship between age and knowledge and chronic energy deficiency in pregnant women at the Glagah Community Health Center, Pakuniran District. This research method uses correlational analytics with a cross-sectional approach which was carried out on 29-31 July 2024. The sample for this research was pregnant women at the Glagah Community Health Center, Pakuniran District, totaling 50 respondents. The technique used in this research is Total Sampling, to collect data using a questionnaire. The research results showed that 40.0% of mothers experienced CED during pregnancy and 60.0% of mothers did not experience CED. The results of this study show that there is a relationship between age and CED in pregnant women with statistical test results of p=0.000 (<0.05) and there is no relationship between knowledge and CED in pregnant women with statistical test results of p=0.426 (<0.05). The conclusion is that there is There is no relationship between age and knowledge with chronic energy deficiency in pregnant women at the Glagah Community Health Center, Pakuniran District.